Assisting in the service of registering the Chairperson of the Election Committee; Collaborative to Increase Community Participation in Kota Baru - Suparno, Suparno; Abidin, Zaenal; Wandi, Wandi; Kuswanto, Kuswanto (CV. Zabags Qu Publish, 2024)
This study aims to analyze the factors that affect community participation in the registration of the Chairman of the Election Committee in Kota Baru. The findings show that public participation is still low, with only 25% of respondents involved, due to lack of information, access gaps, and negative perceptions of the election process. The research methods used include in-depth interviews, focus group discussions, and quantitative surveys. The results show the need for a more inclusive and diverse socialization strategy, the involvement of community leaders, and education about the election process to increase citizens' understanding. The recommendations also include improving the accessibility of information through digital platforms and continuous evaluation of implemented strategies. With these steps, it is hoped that public participation in the registration of the Chairman of the Election Committee can increase, which will ultimately strengthen the quality of democracy in Kota Baru. This research provides valuable insights for election organizers in formulating policies that are more responsive to the community needs